A MicroRNA Cluster in the DLK1-DIO3 Imprinted Region on Chromosome 14q32.2 Is Dysregulated in Metastatic Hepatoblastomas - Honda, Shohei; Chatterjee, Aniruddha; Leichter, Anna L.; Miyagi, Hisayuki; Minato, Masashi; Fujiyoshi, Sunao; Ara, Momoko; Kitagawa, Norihiko; Tanaka, Mio; Tanaka, Yukichi; Shinkai, Masato; Hatanaka, Kanako C.; et al. (Frontiers in Oncology, 2020)
Hepatoblastoma (HB) is the most common malignant liver neoplasm in children. Despite progress in HB therapy, outcomes for patients with metastatic disease remain poor. Dysregulation of miRNA expression is one of the potential epigenetic mechanisms associated with pathogenesis of HB. However, miRNA profiles related to the different stages of HB tissues and cells, in particular of lung metastatic tumor cells, are unknown. In the present study, using array-based miRNA expression and DNA methylation analysis on formalin-fixed paraffin-embedded tissues, we aimed to identify miRNA changes that can discriminate between lung metastatic tumors, primary tumors (fetal and embryonal subtypes) and nontumorous surrounding livers. Our analysis demonstrated that a large cluster of microRNAs and snoRNAs located within the 14q32.2 DLK1-DIO3 region showed a strikingly upregulated expression pattern in HB tumors, especially metastatic tumors, compared to normal liver tissues. This revealed dysregulation of miRNAs similar to that seen in a malignant stem-like subtype of hepatocellular carcinoma associated with poor prognosis. These findings in HB mirror similar findings made in multiple other cancer types. With further analysis this may in future allow stratification of different stages and types of HB tumors based on their miRNA profiles, which could lead to new approaches to diagnosis and treatment in progressive HB patients.